An Exploring Methods in Online Learning: Synchronous and Asynchronous - Fadhilah, Murni; Sutrisna, Sela; Muslimah, Siti Nuri; Ihsan, Muhammad Taufik (ETDC: Indonesian Journal of Research and Educational Review, 2021)
Online learning is becoming increasingly important for several reasons. Especially during the pandemic, since pandemic COVID-19, the teaching and learning process has changed from the traditional face-to-face classroom into online distance learning. Online education is a definite trend that will continue to grow in the years ahead. Online teaching and learning methods can be divided into two groups: synchronous and asynchronous learning. In this case, we will explain the differences and provide some advantages and disadvantages of synchronous and asynchronous learning. Synchronous learning is a learning-oriented interaction that is facilitated by direct, real-time instructions and usually scheduling. Synchronous online learning is commonly facilitated by media such as video conferencing, telecom, live chat, and live streaming. Asynchronous learning means that the learning activity isn't done directly between teachers and learners. The materials have been prepared by the teachers to be accessible to the students. Asynchronous online learning methods involve independent curriculum, streaming video, virtual libraries, and college posts. Synchronous and asynchronous learning use electronic devices, particularly computers and the Internet.